THE IMPACT OF TOURISM INNOVATION ON QUALITY OF LIFE OF RESIDENTS IN THE COMMUNITY: A CASE STUDY OF SUNGAI MELAKA - Aman, Othman; Abdul Manap, Akmal; Ismail, Albert Feisal; Kudus, Norliah; Rahmiati, Filda (Journal of Human Capital Development (JHCD), 2013)
This study investigates the level of awareness and determines tourism innovation impact to the quality of life (QOL) of residents. The main study aims that residents’ of tourism innovation impacts (economic, social, cultural, and environmental) affects their satisfaction of particular life domains. Accordingly, the study proposed three major hypotheses: (1) tourism innovation impacts affects their QOL (economy) in the community, (2) tourism innovation impacts affects their QOL impacts affects their QOL (social) in the community. The sample population consisting of residents residing in Melaka River was surveyed. The sample was proportionally stratified on the basis of tourism development stages covering along the Melaka River form Kampung Pengkalan Rama to Taman Kota Laksamana. 282 respondents completed the survey. Frequency, t-test and correlation analysis were used to test the study. The results revealed that the residents’ Quality Of Life effect to tourism innovation with particular life domains significantly, and their satisfaction with particular life domains influenced their overall life satisfaction. The results indicated that the relationship between the Tourism Innovation and Quality Of Life. The environment impact of tourism and the satisfaction with community well-being were strongest among the other factors to the residents in communities. Keywords: tourism innovation, quality of life, Sungai Melaka, tourism and local community